The Burden of Water Inadequacy on Households in Juba City, South Sudan: A Qualitative Approach - Charles Duku, James Arike; Malek, Nor Malina (Asian Social Work Journal, 2026)
Access to clean and safe water is a fundamental human right and a critical component of public health, yet in Juba City, South Sudan, the situation is dire, with significant portions of the population facing severe water scarcity due to inadequate infrastructure and conflict-driven disruptions. This study investigates the impact of this water scarcity on households in Juba City using a qualitative research methodology. Data were collected through face-to-face interviews, focus group discussions, and key informant interviews with household heads and key stakeholders from various administrative levels in selected payams: Munuki, Juba, and Kator. Purposive, convenience, and critical case sampling were used. Thematic content analysis was employed to identify recurring themes and patterns in the data, revealing the profound effects of inadequate access to clean and safe water on health, economic stability, and social cohesion. The study found that households suffer from increased prevalence of waterborne diseases, significant financial burdens, and heightened social tensions, including conflicts within communities and gender-based violence. The study underscores the urgent need for improved water infrastructure, equitable distribution, and sustainable management practices to mitigate these challenges and enhance the quality of life in Juba City, contributing to the broader goals of Sustainable Development Goal 6.